Integrating disability policies in a post-unification Korea: insights and strategies for social and health equity - Ji Ung Jeong (Discover Social Science and Health)
Abstract This study explores the complexities and potential challenges in harmonizing disability policies following the anticipated unification of North and South Korea. The findings indicate significant disparities between the two regions in areas such as constitutional discrepancies, service provision, disability benefit levels, professionalism of disability support workers, and financial resource management. The study underscores the importance of gradual integration, incremental increases in disability benefits, economic growth, public awareness, and stakeholder engagement in addressing these challenges. By adopting a phased approach and fostering economic prosperity, the unified Korean government can promote equitable access to disability services and enhance societal cohesion. Additionally, proactive measures to improve public understanding and support are essential for legitimizing disability policies and advancing health and social equity.